3-Benzylsulfanyl-1H-1,2,4-triazol-5-amine - Shuai Zhang; Pei-Jiang Liu; Dong-Sheng Ma; Guang-Feng Hou (Acta Crystallographica Section E, 2012)
In the title molecule, C9H10N4S, the dihedral angle between the benzene and triazole rings is 81.05 (5)°. In the crystal, N—H...N hydrogen bonds link the molecules into infinite zigzag chains along [010].